Monetary Policy Announcements and Expectations: Evidence from German Firms - Zeno Enders; Franziska Hünnekes; Gernot J. Müller (Humboldt University Berlin, 2019)
We assess empirically whether monetary policy announcements impact firm expectations. Two features of our data set are key. First, we rely on a survey of production and price expectations of German firms, that is, expectations of actual price setters. Second, we observe the day on which firms submit their answers to the survey. We compare the responses of firms before and after monetary policy surprises and obtain two results. First, firm expectations respond to policy surprises. Second, the response becomes weaker as the surprise becomes bigger. A contractionary surprise of moderate size reduces firm expectations, while a moderate expansionary surprise raises them. Large surprises, both negative and positive, fail to alter expectations. Consistent with this result, we find that many of the ECB's announcements of non-conventional policies did not affect expectations significantly. Overall, our results are consistent with the notion that monetary policy surprises generate an information effect which is endogenous to the size of the policy surprise.
urn:nbn:de:kobv:11-110-18452/21330-9
Keywords: E31; E52; E58; 330; Monetary policy announcements; Firm expectations; Survey data; European Central Bank; Information effect